A Place for Humility : Whitman, Dickinson, and the Natural World - Gerhardt, Christine (Book collections on Project MUSE., 2014)
"A Place for Humility examines Dickinson's and Whitman's poetry in conjunction with this important change in environmental perception, and explores the links between their poetic projects in the context of developing nineteenth-century environmental thought. Gerhardt argues that Dickinson's and Whitman's poetry participates in this shift in different but related ways, and that their involvement with their culture's growing environmental sensibilities constitutes an important connection between their disparate poetic projects"--